Genome-wide comparative methylation analysis reveals the fate of germ stem cells after surrogate production in teleost - Nayak, Rigolin; Franěk, Roman; Laurent, Audrey; Pšenička, Martin (BMC biology, 2024)
BACKGROUND: Surrogate production by germline stem cell transplantation is a powerful method to produce donor-derived gametes via a host, a practice known as surrogacy. The gametes produced by surrogates are often analysed on the basis of their morphology and species-specific genotyping, which enables conclusion to be drawn about the donor's characteristics. However, in-depth information, such as data on epigenetic changes, is rarely acquired. Germ cells develop in close contact with supporting somatic cells during gametogenesis in vertebrates, and we hypothesize that the recipient's gonadal environment may cause epigenetic changes in produced gametes and progeny. Here, we extensively characterize the DNA methylome of donor-derived sperm and their intergenerational effects in both inter- and intraspecific surrogates. RESULTS: We found more than 3000 differentially methylated regions in both the sperm and progeny derived from inter- and intraspecific surrogates. Hypermethylation in the promoter regions of the protocadherin gamma gene in the intraspecific surrogates was found to be associated with germline transmission. On the contrary, gene expression level and the embryonic development of the offspring remained unaffected. We also discovered MAPK/p53 pathway disruption in interspecific surrogates due to promoter hypermethylation and identified that the inefficient removal of meiotic-arrested endogenous germ cells in hybrid gonads led to the production of infertile spermatozoa. CONCLUSIONS: Donor-derived sperm and progeny from inter- and intraspecific surrogates were more globally hypermethylated than those of the donors. The observed changes in DNA methylation marks in the surrogates had no significant phenotypic effects in the offspring.
Keywords: DNA Methylation; Surrogate production; Transplantation; Male; zárodečné buňky; Germ Cells; metylace DNA; Pregnancy; Epigenetic remodelling; těhotenství; Spermatozoa; mužské pohlaví; Germ stem cells; sperma; Stem Cells; Semen; Animals; ženské pohlaví; zvířata; spermie; CpG methylation; Female; kmenové buňky